2008
DOI: 10.1002/adma.200702624
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Infrared Left‐Handed Metamaterials via Double Template‐Assisted Electrochemical Deposition

Abstract: Left-handed metamaterials (LHMs) have recently been the focus of both scientific and engineering communities. [1,2] Simultaneously possessing negative dielectric permittivity e and magnetic permeability m, LHMs exhibit unique electromagnetic properties compared with normal, right-handed materials while still obeying Maxwell's equation and not violating known physical laws.[3] Although obtaining the e < 0 response was relatively easy, the realization of m < 0 response beyond MHz has been a challenge, owing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
56
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 27 publications
0
56
0
Order By: Relevance
“…[11][12][13] However, to the best of our knowledge, research has been rarely reported on negative permittivity or negative permeability directly obtained from conventionally fabricated materials. [14] On the other hand, truly practical applications aspire to large-scale, light-weight, deformable and efficiently processable metamaterials that are not fully realized by those costly and precisely designed structures, or metallic and ceramic materials. Based on the recent success and popularity of polymeric materials in fabricating large-area and flexible electronic devices, [15] it is compelling to consider the fabrication of polymeric metamaterials with the advantages mentioned above.…”
mentioning
confidence: 99%
“…[11][12][13] However, to the best of our knowledge, research has been rarely reported on negative permittivity or negative permeability directly obtained from conventionally fabricated materials. [14] On the other hand, truly practical applications aspire to large-scale, light-weight, deformable and efficiently processable metamaterials that are not fully realized by those costly and precisely designed structures, or metallic and ceramic materials. Based on the recent success and popularity of polymeric materials in fabricating large-area and flexible electronic devices, [15] it is compelling to consider the fabrication of polymeric metamaterials with the advantages mentioned above.…”
mentioning
confidence: 99%
“…Besides, the fabrication of gradient index lens is relatively complicated, and they can only realize limited phase shifts. Recent investigations in metamaterials have opened up new avenues for manufacturing various novel devices [6][7][8][9][10][11][12][13], in which the electromagnetic metasurface as a new approach has attracted tremendous interests of researchers [14][15][16][17][18][19]. The arbitrary modulation of electromagnetic waves could be realized just via ultrathin artificial composite materials, including bending of the direction of propagating waves, abnormal transmission and reflection, and planar lenses.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The samples exhibited a left-handed behavior at an infrared 1.85-mm wavelength. However, this method showed the shortcomings of a multi-step fabrication, such as the preparation of polystyrene (PS) and ZnO template, removal of the PS template, and deposition of the silver dendritic cells array, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1a shows the model of an LHM composed of random dendritic cells and its structure parameters, which is different from the LHMs composed of periodic dendritic cells previously reported. [10][11][12][13][14] It is a sandwich-like structure composed of two layers of random dendritic cells and a dielectric interlayer. The dendritic cells of a large and small size are in a disordered array.…”
Section: Introductionmentioning
confidence: 99%